A novel Hf2CO2/WS2 van der Waals heterostructure as a potential candidate for overall water splitting photocatalyst. (October 2021) - Zhu, Bao; Zhang, Fusheng; Qiu, Jian; Chen, Xianping; Zheng, Kai; Guo, Haojie; Yu, Jiabing; Bao, Jiading
Abstract: In this study, we propose an innovative Hf2 CO2 /WS2 heterostructure with excellent photocatalytic performance for water splitting based on first-principles calculations. The binding energy, and ab initio molecular dynamics (AIMD) simulations exhibit this material's excellent ambient stability. Furthermore, the band structure confirms that the Hf2 CO2 /WS2 heterostructure possesses the intrinsic type-II semiconductor and are well satisfied with the requirements of redox energy level in water splitting reaction. Meanwhile, the charge transfer occurs from Hf2 CO2 to WS2 monolayer, which further induces the separation of photogenerated carriers and prolong the lifetime of carriers. Dramatically high visible-light absorption ( 6.3 × 10 5 cm −1 ) and carrier mobility ( 2.2 × 10 3 cm 2 V -1 s -1 ) are found, which means that the heterostructure has adequate motive force to make the photogenerated carriers separate into different monolayers quickly before recombination. Moreover, according to Gibbs free energy calculation, HER and OER can be triggered spontaneously under the driving of external potential. The results confirm that the thermodynamic feasibility of water splitting on Hf2 CO2 /WS2 heterostructure surface. Hence, these distinctive features endow Hf2 CO2 /WS2 heterostructure with the potential ability of photocatalytic water splitting, which provides a potential avenue for the future experimental project.